THE INFLUENCE OF TRADITIONAL FOOD ON INCIDENCEOF STROKE IN BANDA ACEH - Ade Dita Puteri; Sudirman Sudirman (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Stroke is a partial loss of brain function that occurs suddenly as a result of a blockage or rupture of blood vessels of the brain. Stroke has become an important public health problem in the world, including Indonesia and Aceh. Eating habits which are influenced by culture, customs, religion, and beliefs play an important role in the incidence process of the disease.The aim of this research is to determine the influence of the Acehnese traditional food on the incidence of stroke.This research is descriptive research with cross sectional approach. The population is all outpatients in December 2014 to February 2015 at Zainal Abidin Hospital."Accidental sampling" is the sampling technique that used in this research. The result indicates that Acehnese traditional food influences greatly the incidence of stroke. Some recommendations are related to the Acehnese people to consume foods with balanced nutrition so that it can reduce the incidenceKeywords:traditional food of aceh, stroke